The Role of Targeted Perioperative Nutritional Support and Epigenetic Diet in Mitigating Postoperative Complications of Cystic Echinococcosis - Butaboev , Jasurbek; Shaykhova , Guli; Qosimov , Adham (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
Epidemiological metrics indicate a persistently high rate of postoperative morbidity following cystic echinococcosis interventions, demanding precise evaluations of host metabolic resilience. This prospective, randomized-controlled study (n=126) analyzes the multidimensional dynamics of a targeted epigenetic diet—specifically enriched with methyl donors and polyphenolic modulators—designed to direct hepatic regeneration and suppress systemic inflammatory responses. Empirical clinical data demonstrate that the intervention arm achieved a rapid and significant reduction in serum C-reactive protein (18.4 +/- 4.2 mg/L versus 42.1 +/- 6.8 mg/L) and Tumor Necrosis Factor-alpha levels by postoperative day 5. Analytical outputs confirm that integrating this targeted nutritional profiling optimizes early functional recovery, dropping specific localized complications to 4.7 percent (compared to 17.4 percent in the isocaloric control group) and drastically reducing the mean hospital stay duration from 10.2 +/- 2.4 days to 6.5 +/- 1.1 days. The dynamics of the obtained results mandate an urgent paradigm shift from passive post-surgical feeding toward active, prehabilitative pharmaconutritional interventions, establishing a rigorous foundation for future hepatobiliary treatment strategies.